2019
DOI: 10.1038/s41598-019-54418-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly cooperative fluorescence switching of self-assembled squaraine dye at tunable threshold temperatures using thermosensitive nanovesicles for optical sensing and imaging

Abstract: Thermosensitive fluorescent dyes can convert thermal signals into optical signals as a molecular nanoprobe. These nanoprobes are playing an increasingly important part in optical temperature sensing and imaging at the nano- and microscale. However, the ability of a fluorescent dye itself has sensitivity and accuracy limitations. Here we present a molecular strategy based on self-assembly to overcome such limitations. We found that thermosensitive nanovesicles composed of lipids and a unique fluorescent dye exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…However, when the temperature was increased to > 42 °C, the liposomes changed to be in a liquid crystalline state and the fluorescence intensity dramatically increased. This fluorescence switching at the phase transition temperature of the liposomes was in good agreement with previous reports of liposomes containing SQR22, which correspond to the PEG-TLip in this study 18 . The results showed that the attachment of biotin on the surface of the liposomes had little effect on the temperature-responsive fluorescence properties, indicating that the PEG-TLip can be used as a negative control for the biotin-TLip.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, when the temperature was increased to > 42 °C, the liposomes changed to be in a liquid crystalline state and the fluorescence intensity dramatically increased. This fluorescence switching at the phase transition temperature of the liposomes was in good agreement with previous reports of liposomes containing SQR22, which correspond to the PEG-TLip in this study 18 . The results showed that the attachment of biotin on the surface of the liposomes had little effect on the temperature-responsive fluorescence properties, indicating that the PEG-TLip can be used as a negative control for the biotin-TLip.…”
Section: Resultssupporting
confidence: 93%
“…DPPC and DHSG were purchased from Nippon Fine Chemical (Tokyo, Japan), while PEG 5000 -DSPE was purchased from NOF Corporation (Tokyo, Japan). The fluorescent dye SQR22 was synthesized according to a previous report 18 . Tert-butyl alcohol (t-BuOH) was used to lyophilize the lipids and was purchased from Kanto Chemical (Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis and characterization of the fluorescent dye (2-[4-(dibutylamino)phenyl]-4-[(3,3-dimethyl-3 H -indol-2-yl)methylene]-3-hydroxycyclobut-2-en-1-one, SQR22) were reported previously. 28 SQR22 was obtained by custom synthesis from the NARD Institute (Kobe, Japan). Octyl glucoside (OG), which was used to destroy the liposomal structure for further lipid concentration analysis, was obtained from Carbosynth (Berkshire, UK).…”
Section: Methodsmentioning
confidence: 99%